Sistem Monitoring Daya Listrik Berbasis Internet of Things Menggunakan Application Programming Interface (API) - Denny Wijanarko (Jurnal Teknologi Informasi dan Terapan, 2023)
The use of Internet of Things technology in power monitoring systems has become a popular solution to overcome electricity consumption problems. PT Indonesia Comnets Plus (PLN Icon Plus) is a subsidiary of PLN which operates in the field of information and communications technology. To support its business activities, until the end of 2021, this company has 26 representative offices spread throughout Indonesia. ICON+ KP Yogyakarta is one of these representative offices. Unfortunately, the ICON+ Yogyakarta Branch office often experiences power outages due to the use of electrical power that exceeds the available capacity. For this reason, this research developed an internet of things-based electrical power monitoring system to monitor electrical power usage at PT ICON+ Yogyakarta in real time.